Feminism and citizenship - Voet,Rian (Politics and culture (London, England), 1998)
Until recently, feminist theory and citizenship theory have seemed two distinct areas, with writers in both camps seldom discussing the other's work. Feminism and Citizenship challenges this silence, arguing for the need to collect the debates around citizenship and feminism. The author provides an original reflection upon the key issues in political theory and advocates a unique feminist intervention into the sub-themes of citizenship, including liberty, rights, social equality, political identity, political representation and political judgement. Rian Voet moves to develop a feminist notion of citizenship by discussing critically citizenship theories and identifying rudimentary feminist theories of citizenship. However, unlike most feminist texts which insist that political theory takes feminism and gender more seriously, Voet emphasizes that feminist theory should reflect more seriously upon citizenship.